The Evaluation of Metaphoric Perceptions of the Concept of “Geography” by Geography Teacher Candidates - Kaya, Baştürk; Aladag, Caner (Acta Paedagogica Vilnensia, 2024)
This study was carried out to reveal the metaphors by geography teacher candidates about the concept of “Geography.” The data of the study were collected with qualitative research method and the study was carried out on the pattern of phenomenology. The data were subjected to content analysis. In order to determine the students’ perceptions about the concept of geography, a semistructured form was prepared, and this form included the sentence of “Geography is like a/an ..........., because ........” Students were asked to complete this sentence in the form. When the findings of the study were evaluated, it was seen that 86 valid metaphors had been produced by the students. These metaphors were coded in terms of their common features and 8 different conceptual categories were created. The prominent ones of these categories were “Geography as the source of discovery and learning,” “Geography as the source of diversity,” “Geography as similar to humanity,” “Geography as the source of peace and acceptance,” and metaphor numbers and frequencies of these categories were high.
Keywords: Methapor; Geography; Teacher candidate; Qualitative research; Perception